Efficacy and safety comparison of esketamine-propofol with nalbuphine-propofol for upper gastrointestinal endoscopy in children: a multi-center randomized controlled trial - Zheng, Xiaosu; Huang, Jinjin; Wei, Sisi; Tao, Yingying; Shen, Yang; Wang, Yanting; He, Pan; Zhang, Mazhong; Sun, Ying (Frontiers in Pediatrics, 2023)
Purpose: The appropriate sedation level and anesthetics combination could increase the efficiency and both pediatric patients and endoscopists satisfaction during the upper gastrointestinal endoscopy. Propofol was the most extensively used basic intravenous anesthetic in clinical practice. The aim of the study was to explore the superiority and safety of propofol with nalbuphine or esketamine in children undergoing diagnostic upper endoscopy. Methods: In this multicenter study, 200 children undergoing painless upper gastrointestinal endoscopy were randomly divided into esketamine group (100 cases) and nalbuphine group (100 cases). The patients in esketamine group were given esketamine 0.5 mg/kg and propofol 2 mg/kg intravenously, while the children in the nalbuphine group were given nalbuphine 0.2 mg/kg and propofol 2 mg/kg. The “failure” for the insertion of the endoscope was recorded especially for the first attempt. The primary outcome was success rate for endoscope insertion. The perioperative adverse events, gastroenterologist’s satisfaction and other secondary outcomes were also recorded, such as the duration for examination and awakening, some important vital signs and scores for the Face, Leg, Activity, Cry and Consolability (FLACC) scale and the Pediatric Anesthesia Emergence Delirium (PAED) scale. Results: Compared with the nalbuphine group, the esketamine group had a higher success rate (97% vs 66%；p<0.01). The heart rate and mean arterial pressure after intraoperative administration in the esketamine group were higher than those in the nalbuphine group, while the delirium incidence during awakening was higher in esketamine group (all p<0.05). Conclusion: Among children who completed painless diagnostic upper gastrointestinal endoscopy under deep sedation/anesthesia, the success rate of esketamine group was higher than that of nalbuphine group, propofol-related hemodynamic changes were reduced accordingly, while the incidence of esketamine-related adverse effects could be high.